Impact of prophylactic unilateral central neck dissection needed for patients with papillary thyroid microcarcinoma - Ryu, Young Jae (Gland Surg, 2020)
BACKGROUND: Papillary thyroid microcarcinoma (PTMC), the increase in the diagnosis of which has led to an overall rise in the diagnostic rate of thyroid malignancies, is generally managed through a reduction in the surgical extent. Nevertheless, a considerable number of patients with PTMC experience subclinical central lymph node (LN) metastases following prophylactic central neck dissection (CND). This study aimed to investigate the impact of prophylactic CND on locoregional recurrence in PTMC patients who underwent hemithyroidectomy. METHODS: We reviewed the medical records of 1,071 patients with clinically LN-negative PTMC who underwent hemithyroidectomy between 2004 and 2012. Cox proportional hazards regression analysis was performed to investigate the predictive factors for recurrence. The median follow-up duration was 79 months (range, 12–176 months). RESULTS: Totally, 613 patients underwent hemithyroidectomy only, whereas 458 underwent hemithyroidectomy plus prophylactic unilateral CND. Recurrence was observed in 27 patients (eight and 19 patients in the prophylactic and non-prophylactic CND groups, respectively). Patients with a tumor size ≤6 mm (hazard ratio, 2.927; 95% confidence interval, 1.372–6.245; P=0.005) had favorable recurrence-free survival (RFS); however, there was no relationship between prophylactic unilateral CND and RFS. CONCLUSIONS: The incidence of locoregional recurrence was low in patients with PTMC who underwent hemithyroidectomy. In addition, prophylactic unilateral CND performance was not associated with RFS in PTMC. Accordingly, the use of prophylactic unilateral CND for clinically LN-negative PTMC should be avoided.